Translating Rhetorical Interrogation in the Qur’an: A Comparative Analysis of Literal and Interpretive Approaches - Teta Mohamed, Khadir Fouad Soufiane (Journal of Informatics Education and Research, 2025)
This article addresses the issue of conveying the rhetorical purposes of interrogative style in the Qur’an when translated into English. Interrogation constitutes one of the most prominent Qur’anic styles, carrying multiple rhetorical intentions that go beyond its literal interrogative meaning, such as affirmation, reproach, astonishment, and denial. Using a comparative analytical method, the study compares George Sale’s translation (1734) with that of Muhammad Taqi-ud-Din al-Hilali and Muhammad Muhsin Khan (1996). The findings reveal that literal translation often fails to convey the rhetorical depth of the Qur’anic text, while interpretive translation tends to bring these meanings closer to the non-Arabic reader, though sometimes at the expense of Qur’anic brevity and stylistic power. The article concludes that addressing the rhetorical purposes of interrogation requires balancing fidelity to the original text with sensitivity to its rhetorical context, and it proposes adopting balanced strategies that preserve the argumentative intent of the Qur’anic discourse.